The Antimicrobial Potential of the Hop (Humulus lupulus L.) Extract against Staphylococcus aureus and Oral Streptococci - Alyona Khaliullina; Alyona Kolesnikova; Leysan Khairullina; Olga Morgatskaya; Dilyara Shakirova; Sergey Patov; Polina Nekrasova; Mikhail Bogachev; Vladimir Kurkin; Elena Trizna; Airat Kayumov (MDPI AG, 2024)
Plant extracts are in the focus of the pharmaceutical industry as potential antimicrobials for oral care due to their high antimicrobial activity coupled with low production costs and safety for eukaryotic cells. Here, we show that the extract from Hop (Humulus lupulus L.) exhibits antimicrobial activity against Staphylococcus aureus and Streptococci in both planktonic and biofilm-embedded forms. An extract was prepared by acetone extraction from hop infructescences, followed by purification and solubilization of the remaining fraction in ethanol. The effect of the extract on S. aureus (MSSA and MRSA) was comparable with the reference antibiotics (amikacin, ciprofloxacin, and ceftriaxone) and did not depend on the bacterial resistance to methicillin. The extract also demonstrated synergy with amikacin on six S. aureus clinical isolates, on four of six isolates with ciprofloxacin, and on three of six isolates with ceftriaxone. On various Streptococci, while demonstrating lower antimicrobial activity, an extract exhibited a considerable synergistic effect in combination with two of three of these antibiotics, decreasing their MIC up to 512-fold. Moreover, the extract was able to penetrate S. aureus and S. mutans biofilms, leading to almost complete bacterial death within them. The thin-layer chromatography and LC-MS of the extract revealed the presence of prenylated flavonoids (2',4',6',4-tetrahydroxy-3'-geranylchalcone) and acylphloroglucides (cohumulone, colupulone, humulone, and lupulone), apparently responsible for the observed antimicrobial activity and ability to increase the efficiency of antibiotics. Taken together, these data suggest an extract from H. lupulus as a promising antimicrobial agent for use both as a solely antiseptic and to potentiate conventional antimicrobials.